1999
DOI: 10.1007/bf02494755
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolysis of trichlorosilane in the presence of chloroform

Abstract: The pyrolysis of trichlorosilane in the presence of different amounts of chloroform and the copyrolysis of HSiCI 3 with buta-l,3-diene in the presence of I tool.% chloroform were studied. The enthatpies of formation of products resulting from the pyrolysis of HSiCI 3 in the presence of chloroform were calculated by the quantum chemical method. Based on the thermochemical data as well as data from GLC and mass spectrometry, it was concluded from the condensate composition that introduction of chloroform into th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…On the one hand, the chlorine free radical facilitates the transformation of trichlorosilane to the trichlorosilyl radical (Step ⑬); on the other hand, it accelerates the transformation of the trichlorosilyl radical to tetrachlorosilane (Step ⑰), so the selectivity to phenyltrichlorosilane decreases. Steps ⑥ to ⑫ show the most probable step for dichlorosilylene generation [11]. Some other possible steps of dichlorosilylene generation are shown as Steps ⑩ and ⑪.…”
Section: Reaction Schemementioning
confidence: 99%
See 3 more Smart Citations
“…On the one hand, the chlorine free radical facilitates the transformation of trichlorosilane to the trichlorosilyl radical (Step ⑬); on the other hand, it accelerates the transformation of the trichlorosilyl radical to tetrachlorosilane (Step ⑰), so the selectivity to phenyltrichlorosilane decreases. Steps ⑥ to ⑫ show the most probable step for dichlorosilylene generation [11]. Some other possible steps of dichlorosilylene generation are shown as Steps ⑩ and ⑪.…”
Section: Reaction Schemementioning
confidence: 99%
“…(6)]. Heinicke investigated the copyrolysis of trichlorosilane with chlorobenzene and 1,3-butadiene without a free radical initiator and detected no dichlorosilylene [14], while Krasnova showed that the introduction of chloroform favored the generation of silylenes [11]. Several researches used conjugated dienes to react with dichlorosilylenes [19][20][21][22].…”
Section: Proposed Reaction Mechanismmentioning
confidence: 99%
See 2 more Smart Citations